2014
DOI: 10.1007/s11746-014-2420-7
|View full text |Cite
|
Sign up to set email alerts
|

Fats from Chemically Interesterified High‐Oleic Sunflower Oil and Fully Hydrogenated Palm Oil

Abstract: Chemical interesterification of different lipid materials has considerable potential for the production of a wide variety of special fats with improved functional and nutritional properties. The present study aimed to evaluate the chemical interesterification of blends of high‐oleic sunflower oil (HOSO) and fully hydrogenated palm oil (FHPO) in the ratios (% w/w) of 80:20, 70:30, 60:40 and 50:50. The blends were characterized in triacylglycerol composition, melting point, solid fat content and crystallization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 21 publications
5
20
1
2
Order By: Relevance
“…The IV of partially hydrogenated palm oil was with 41.6 ± 1.0 expectedly lower . Fully hydrogenated palm oil showed an IV of 4.4 ± 0.8, which is higher than the typical value for fully hydrogenated oils around 1.5 …”
Section: Resultscontrasting
confidence: 57%
“…The IV of partially hydrogenated palm oil was with 41.6 ± 1.0 expectedly lower . Fully hydrogenated palm oil showed an IV of 4.4 ± 0.8, which is higher than the typical value for fully hydrogenated oils around 1.5 …”
Section: Resultscontrasting
confidence: 57%
“…This behavior is similar to that reported by Jahurul et al [32], who analyzed hard cocoa butter replacers from mango fat seed and palm stearin, finding that the oleic acid in blends of TAGs had a lowering effect over SFC and its melting point. Meanwhile, Masuchi et al [33] observed this same behavior in fats from chemically interesterified high-oleic sunflower oil and fully hydrogenated palm oil.…”
Section: Solid Fat Content (Sfc) Determinationmentioning
confidence: 72%
“…However, when two lipid classes with such distinct chemical composition, such as oils and hardfats, are mixed, the physicochemical properties of the mixture are not necessarily the same as those of the original components, which may result in incompatibility. A monotonic behavior, when high‐melting triacylglycerols are solubilized in the liquid fraction, were observed in binary systems containing soybean oil and soybean hardfat (Ribeiro, Grimaldi, Gioielli, & Gonçalves, ), soybean oil and crambe hardfat (Guedes et al., ), and high oleic sunflower oil and palm hardfat (Masuchi et al., ). The authors found a lower incompatibility in all binary systems by the chemical interesterification, which promoted greater heterogeneity in the composition of triacylglycerols, increasing their solubility in the solid state, thus leading to the formation of solid‐solid solutions.…”
Section: Lipid Modification Processesmentioning
confidence: 99%
“…However, the chemical interesterification, which is the redistribution of the fatty acids on the glycerol molecule, has high cost when compared to the partial hydrogenation (Mba, Dumont, & Ngadi, 2015), involving high consumption of water and energy (Patterson, 2010), once deodorization and further clarification of the interesterified lipid base is required (Holm & Cowan, 2008). In addition, the interesterified lipid base exhibits reduced oxidative stability when compared to the original raw materials (Kowalska, Zbikowska, & Tarnowska, 2015;Zeb & Murkovic, 2013), and minor compounds, such as mono-and diacylglycerols, which delay the crystallization events necessary to structure the lipid base to form a semi-solid system (Masuchi et al, 2014). From the nutritional point of view, the main issues are related to the increase in saturated fatty acids concentration, whose reduction in diet is globally indicated to reduce the risk of cardiovascular disease, once they are associated with the increase in plasma cholesterol (Wassell, Bonwick, Smith, Almiron-Roig, & Young, 2010) and the possible negative nutritional effects due to the formation of isomers in the sn-2 position of triacylglycerols during interesterification (Domingues, Ming, Ribeiro, & Gonçalves, 2015;Karupaiah & Sundram, 2007).…”
Section: Lipid Modification Processesmentioning
confidence: 99%
See 1 more Smart Citation